Professional Competence of Future Primary School Teachers in the Context of an Updated Educational System - Suguraliyeva, Aliya; Bakhtiyarova, Gulshat; Abil, Akmaral; Kapina, Elmira; Taganova, Aru (Journal of Teaching and Learning, 2026)
This study explores the essential competencies required for future primary school teachers within the context of updated educational systems, focusing on the evolving demands of modern education. Utilizing a mixed-methods approach, the research combines qualitative and quantitative techniques to analyze academic literature, educational policies, and teacher training programs. The analysis highlights key competencies, including planning, communication, social interaction, cooperation, and educational skills, which are crucial for effective teaching. The findings underscore the importance of continuous professional development, critical reflection, and the integration of technology in teacher training. The study also addresses the challenges posed by contemporary issues, including military conflicts and the necessity for adaptable teaching strategies. By examining various competency models and frameworks, the research provides insights into best practices in teacher education, emphasizing a shift from traditional teaching methods to competency-based approaches that align with current educational reforms and technological advancements.